Structure and efficiency of onion market in Karnataka - K B, Vedamurthy,; S J, Prashanth; T R, Shashidhar (Journal of Postharvest Technology, 2021)
Farmers in Karnataka face high levels of distress due to low price realization and lower productivity. The marketing system plays a crucial role in addressing this issue, especially for onion, which covers 67% of the area under vegetables in the state. The Lorenz curve and Gini coefficient were used to assess competitiveness, while the Toda-Yamamoto (T-Y) method examined price integration and efficiency. The findings showed that Bengaluru, which accounted for over 65% of onion arrivals, had a high concentration of traders, with just 3% of traders handling 50% of onions in 2017-18. This indicates an extremely high level of concentration, with farmers becoming price takers. Integration and efficiency analyses showed that most markets had two-way Granger causality and were interdependent with Bengaluru. However, the high concentration of traders meant that price discovery was inefficient, leaving farmers as mute spectators. To address this issue, market intervention through information, innovations, and institutions is necessary. The government must provide institutional support and access to information, better marketing infrastructure, and innovative marketing techniques. This will help improve price discovery, reduce market concentration, and provide better market access to farmers. Farmers should also be encouraged to diversify their crops, utilize modern technology, and receive better credit facilities. These measures will help reduce the farmers’ dependence on a single crop, mitigate price fluctuations, and increase productivity. In conclusion, a competitive and efficient marketing system is critical to alleviating the distress faced by farmers in Karnataka.